Gengivoplastia associada a osteotomia para harmonização do sorriso - Pimenta, Guilherme Silveira Coelho [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The aesthetics within dentistry encompasses multidisciplinary procedures, among them, surgical techniques for correction of imperfections in the smile. The gingival smile associated with the short clinical crown compromises the aesthetics of the smile and interferes with the patient's social behavior and self-esteem. Looking for aesthetic and functional results, several techniques are proposed for gingival tissue removal. Thus the present study aims to present a clinical case submitted to gingivoplasty associated with osteotomy. Patient, 22 years old, masculine, non smoker and with good oral hygiene, presented the periodontics discipline of the Faculty of Dentistry of Araçatuba - UNESP, with complaint of infant smile, short teeth and unfavorable aesthetics. After the diagnosis of altered passive eruption, the techniques of gingivoplasty and osteotomy were planned and executed to correct the smile aesthetics. After the surgical treatment and follow up of the case for 24 months, it was verified that the association of the two techniques obtained a final clinical success, removing excess gingival tissue, increasing the clinical crown and returning the biological space conferring aesthetic satisfaction of the patient and smile harmony

A estética dentro da odontologia engloba procedimentos multidisciplinares, dentre eles, técnicas cirúrgicas para correções de imperfeições no sorriso. O sorriso gengival associado a coroa clínica curta comprometem a estética do sorriso e interfere no comportamento social e auto-estima do paciente. Buscando resultados estéticos e funcionais, várias técnicas são propostas para a remoção do tecido gengival. Assim o presente estudo tem como objetivo apresentar um caso clínico submetido a gengivoplastia associado a osteotomia. Paciente de 22 anos, gênero masculino, não fumante e com boa higiene bucal, apresentou se a disciplina de Periodontia da Faculdade de Odontologia de Araçatuba - UNESP, com queixa de sorriso infantil, dentes curtos e estética desfavorável. Após o diagnóstico de erupção passiva alterada, foi planejado e executado as técnicas de gengivoplastia e osteotomia para correção da estética do sorriso. Após o tratamento cirúrgico e acompanhamento do caso durante 24 meses, verificou se que a associação das duas técnicas obteve sucesso clínico final, removendo o tecido gengival em excesso,aumentando a coroa clínica e devolvendo o espaço biológico conferindo satisfação estética do paciente e harmonia do sorriso
Keywords: Sorriso; Gengivoplastia; Osteotomia; Smiling